Efeitos bioquímicos e fisiológicos do chumbo em plantas de quitoco (Pluchea sagittalis): possível papel fitorremediador - Rossato, Liana Verônica (2010)
Lead (Pb) is one of the most abundant, globally distributed toxic elements. Soil, water and air contamination by Pb leads to its accumulation in fish, mammals, and plants, and thus to human intoxication through food. Due to the hazardous effects to the ecosystem, it is necessary that contaminated soils be rehabilitated. Phytoremediation is a cheap technique that can be utilized with this objective. However, it is necessary to know about plant behavior during metal exposure. Therefore, the aim of this study was to characterize physiological and biochemical aspects of Pb toxicity in roots and leaves of different developmental stages (apex, middle, and basal regions) in P. sagittalis plants. Plants were exposed to five Pb levels: (0, 200, 400, 600, 1000 μM) for 30 days. Parameters such as growth, tissue Pb concentration and content, toxicity indicators (d-aminolevulinic acid dehidratase, d-ALA-D, activity), oxidative damage markers (TBARS, lipid peroxidation, and H2O2 concentration) and enzymatic (superoxide dismutase, SOD, catalase, CAT, and ascorbate peroxidase, APX) and non-enzymatic (non-protein thiols, NPSH, ascorbic acid, AsA) antioxidants were investigated. Tissue Pb concentration increased with external Pb levels causing a decrease in the consumption of nutrient solution and transpiration ratio. Moreover, root and shoot fresh weight, leaf area, shoot length and d-ALA-D activity decreased upon addition of Pb treatments. On the other hand, dry weight of shoots and roots and chlorophyll and carotenoids concentrations were not affected. Both fresh and dry weight of roots increased at 200 μM Pb, when compared to control. The index of tolerance of roots and shoots of P. sagittalis decrease at higher Pb concentrations. However, the roots were more tolerant to Pb than shoots. Lipid peroxidation and hydrogen peroxide (H2O2) concentration both in roots and leaves increased with increasing Pb levels. APX activity increased by Pb treatments in all plant parts, while SOD activity increased in leaves and it was not affected in roots. CAT activity in leaves from the apex shoot was not affected by Pb; however, in other plant parts its activity increased. Pb toxicity caused increase in NPSH concentration in shoot parts, whereas no significant difference was observed in roots. AsA concentration increased with increasing Pb levels. These results suggest that Pb induces oxidative stress in P. sagittalis and that elevated activity of antioxidative enzymes could serve as important components of antioxidative defense mechanism against oxidative injury, demonstrating tolerance and possible use of these plants for reclamation of Pb contaminated soils.